AGENDA 21 SECTION IV AND GANDHIAN PHILOSOPHY – A REVIEW - KUMAR, SANJAY (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2015)
The Earth Summit 1992 resulted into five documents, Rio Declaration on Environment and Development, Forest Principles, Convention on Biological Diversity, Framework Convention on Climate Change (UNFCCC) and Agenda 21. Agenda 21 is a blueprint for sustainable development into the 21" Century. There are 40 chapters of Agenda 21, divided into four main sections. It includes combating poverty, changing consumption pattern, promoting health, atmospheric protection, combating deforestation, conservation of biological diversity (biodiversity), and control of pollution, the roles of children, youth, women, NGOs, local authorities, technology transfer, promoting education, public awareness & training, etc. Agenda 21 is a vast document that has brought out many issues. Due to space restrictions only two chapters from section IV are taken here for comparison with Gandhaian philosophy. It is striking to note that most of the issues forming integral part of Agenda 21 have already brought forth by Mahatma Gandhi (Mohanndas Karamchand Gandhi) a century back when there were absolutely no environmental degradation and pollution concerns. All the problems were anticipated long ago and given probable solution. There may be repetition of certain points and quotations at more than one place in the article because of their relevance.